Criteria-based Certification and Validation of Online Pharmacies: Opportunities for Improved Quality and Safety - Özlem H. Ersin; David M. Naistat (University of Minnesota Libraries Publishing, 2015)
Objectives: The objective of this study was to explore the conformity of online sites with established quality standards. Methods: Online pharmacies with the NABP Verified Internet Pharmacy Practice Sites (VIPPS) designation were scrutinized for their conformity with select criteria established by the National Association of Board of Pharmacies (NABP) and FDA consumer guidelines. Results: 36 VIPPS certified online pharmacy sites were included in the study. The sites were examined against VIPPS and FDA standards. The criteria related to the design and content of the web site and to the pharmaceutical services being offered through the site. Lack of clear terminological distinction between "online pharmacy" (a business) and "online site" (a tool for a business) was problematic. Sites did not adhere to uniform design principles. The scope and availability of pharmaceutical services for online consumers were not readily apparent. Conclusion: The very legitimacy of existing criteria for online pharmacies remains to be established. Significant opportunities exist to improve the quality and scope of policies and to tie them more closely to longstanding best-practices in areas such as web usability and pharmaceutical care. Revision recommendations for VIPPS criteria are discussed.   Type: Original Research